Model Return Sharia Shares of Companies Registered in Jakarta Islamic Index (JII) for the 2012-2022 - Desi Ika; Andri Soemitra; Nurlaila; Al-Mahdi (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
This study develops a return model for Sharia-compliant stocks listed in the Jakarta Islamic Index (JII) from 2012 to 2022 examining the influence of macroeconomic and corporate governance factors. Specifically, it investigates the roles of Inflation, the Bank Indonesia Sharia Certificate Rate (SBIS), Islamic Corporate Governance (ICG), and Islamic Corporate Social Responsibility (ICSR) on firm profitability and Sharia stock returns. It also analyzes the mediating effect of profitability on stock returns. This research addresses a global concern regarding sustainable and ethical investment in Islamic capital markets, offering insights into how Sharia-compliant companies perform under financial and social governance standards. Employing a quantitative approach with Structural Equation Modeling (SEM) via SmartPLS, the study examines eight consistently listed companies in the JII over 11 years using purposive sampling. Results reveal that ICG and ICSR significantly enhance both profitability and stock returns, affirming their strategic value in Islamic equity markets. Inflation and SBIS, however, show no significant direct or indirect effect on profitability or returns. This model contributes novel empirical evidence on return behavior in Islamic equities, supporting global efforts toward ethical finance. Future research should expand the dataset and explore cross-country comparisons within Islamic stock indices.